Recontextualization of the Constitutional Court's Decision on the Presidential Age Limit in @Kompascom and @TVOneNews - Arkida, Teisar; Sumarlam, Sumarlam (Darul Yasin Al Sys, 2024)
This paper aims to analyze the recontextualization of reports on the Constitutional Court's decision regarding the requirements for presidential and vice presidential candidates on Twitter/ X accounts of @kompascom and @tvonenews. A qualitative analysis were conducted using Norman Fairclough's critical discourse analysis approach, which includes description, interpretation, and explanation. The text description analysis utilized appraisal framework. According to text analysis of @kompascom, the Constitutional Court's decision is portrayed negatively. The article describes negative happiness, negative satisfaction, and negative quality as reasons for people's sadness and anger. The decision is considered to be full of fabrications and is seen as paving the way for Gibran to become Prabowo's vice presidential candidate. The news report from @tvonenews describes the Constitutional Court's decision as interesting due to its positive impact on Gibran's opportunity to run as a vice presidential candidate. However, the report also indirectly highlights a negative aspect of the decision by reporting that Anwar Usman committed a serious ethical violation. (2) According to the discourse practice analysis, @kompascom connects the Constitutional Court's decision to Gibran's candidacy, while @tvonenews connects it more to Anwar Usman's ethical violations. (3) The analysis of social practices reveals changes and stabilizations of social values in various matters, including public opinion, political polarization, and youth involvement. The latter is key to achieving a balance between stability and change, as well as upholding the rule of law.